Screening of 23 β-lactams in foodstuffs by LC–MS/MS using an alkaline QuEChERS-like extraction. Issue 4 (3rd April 2018) - Bessaire, Thomas; Mujahid, Claudia; Beck, Andrea; Tarres, Adrienne; Savoy, Marie-Claude; Woo, Pei-Mun; Mottier, Pascal; Desmarchelier, Aurélien
ABSTRACT: A fast and robust high performance LC–MS/MS screening method was developed for the analysis of β-lactam antibiotics in foods of animal origin: eggs, raw milk, processed dairy ingredients, infant formula, and meat- and fish-based products including baby foods. QuEChERS extraction with some adaptations enabled 23 drugs to be simultaneously monitored. Screening target concentrations were set at levels adequate to ensure compliance with current European, Chinese, US and Canadian regulations. The method was fully validated according to the European Community Reference Laboratories Residues Guidelines using 93 food samples of different composition. False-negative and false-positive rates were below 5% for all analytes. The method is adequate for use in high-routine laboratories. A 1-year study was additionally conducted to assess the stability of the 23 analytes in the working standard solution.